Metal oxide nanofibers in solar cells - Ling, Jin Kiong; Jose, Rajan (Elsevier Inc., 2021)
The motivation to improve the performance of sensitized photovoltaic (PV) cells by enhancing both the surface area and carrier diffusion properties of its photoanode had drawn attention toward utilizing metal oxide nanofibers (NFs). Owing to the anisotropic carrier transport characteristic, NFs had surpassed the nanoparticles analog in achieving higher photoconversion efficiency (PCE) in sensitized PV while preserving the benefit of high surface area. However, the higher density of delocalized trap states in nanostructured materials, compared to the bulk materials, hampered further improvement in the PCE of NF-based sensitized PV cells. This chapter offers a brief explanation of the photoconversion mechanism of sensitized PV cells, followed by a discussion of the importance of utilizing metal oxide NFs as the charge extractor for this specific application. Details on the formation of delocalized trap states and how it impairs the carrier diffusion coefficient are provided. Some techniques for eradicating the effect brought about by the delocalized trap states are offered and reviewed, and challenges for future development of metal oxide NF-based sensitized PV cells are discussed.